Information and communication technologies, a tool for risk prevention and accident management on sea ice - Elise Lépy (Netcom)
Marine ice melting topic is a repetitive phenomenon in alarmist speeches on climate change. The present positive evolution of air temperatures has in all probability many impacts on the environment and more or less directly on societies. Face to the temperature elevation, the ice pack is undergone to an important temporal variability of ice growth and melting. Human populations can be exposed to meteorological and ice hazards engendering a societal risk. The purpose of this paper is to better understand how ICT get integrated into the risk question through the example of the Bay of Bothnia in the northern extremity of the Baltic Sea. The study deals with the way that Finnish society, advanced in the ICT field, faces to new technology use in risk prevention and accident management on sea ice.